Divine Values ​​in Forming Community Integrity: An Analysis of the First Principle of Pancasila - Fikri, Muhammad Zaki (Maliki Interdisciplinary Journal, 2026)
The first principle of Pancasila, "Belief in the One and Only God," ideally serves as a moral bulwark that guides societal integrity through profound spiritual understanding. However, the current reality demonstrates a sharp paradox where high levels of formal religiosity are not directly proportional to social integrity, marked by rampant corrupt practices and ethical degradation in the social environment. Theoretically, integrity in this context should be viewed as a divine behavior based on responsibility that places God as the highest moral guide, going beyond mere administrative oversight. The urgency of this study lies in the urgent need to address the systemic moral crisis that can no longer be adequately addressed through a formal legal approach without the support of a solid ethical foundation. Therefore, this study aims to analyze the substantive role of the value of the Godhead in building collective societal integrity and formulate a strategy for its internalization so that the values ​​of Pancasila do not stop at formality, but also transform into a real ethical compass for realizing a clean and dignified national life..